Answer is b ,-4x^2 - 13y^2
Answer:
ƒ(x) = (x - 2)^2 + 1
Step-by-step explanation:
To make f(x) be a translation of the graph of g(x) by (h, k), write it as ...
f(x) = g(x -h) +k
You want to translate g(x) = x^2 by (2, 1), 2 units right and 1 unit up, so the function f(x) is ...
f(x) = g(x -2) +1
Answer:
324
Step-by-step explanation:
$20
One loaf costs 2 dollars- Multiply both sides of the ratio by 10 and you get 20 as ur answer.
Answer:
option C is your right answer
Step-by-step explanation:
have a nice day!!